Digital Book and Its Evolution - Gudinavičius, Arūnas (Knygotyra, 2012)
Based on the analysis of scientific papers and sources, the presumptions on the future of digital book are analyzed and most important of them are picked out: the birth of the digital computer (as the medium of the digital book reading and creating), the rise of hypertext (as a new influence upon reading and writing digital books) and the foundation of the internet prototype (as a new medium for publishing and accessing digital books). The most important facts in the history of digital book are picked out and analyzed.According to product life cycle theory, the evolution of the digital book is proposed to be divided into several stages: the stage before the digital book (the presumptions of origin, 1946–1971), the beginning of the digital book (first stage, 1971–2001), and the growth of the digital book (second stage starting from 2001).The present situation of the digital book in the product life cycle is shown and some future prognoses are presented.
Keywords: digital book; e-book; e-book quality